The Influence Of Knowledge-Based Hrm Practices And Intellectual Capital On Innovation Performance Of Private Hospital Employees - Imam Santoso; Ratna Indrawati; Sukmo Hadi Nugroho (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Innovation performance is important in influencing human resource management to be able to bring progress to the hospital. Innovation performance is strongly influenced by many aspects, such as knowledge-based human resource management which influences intellectual capital (human capital, structural capital, and relational capital). This research involved 81 hospitals and 221 employees (managers/leaders of private hospitals) in the Greater Jakarta area. This type of research is deductive, and data collection by distributing questionnaires. The analytical method used is the Structural Equation Model (SEM). The results obtained from this study are that knowledge-based HRM practices have direct and indirect effects on human capital, structural capital, and innovation performance. Furthermore, human capital can influence structural capital and innovation performance. Human capital also plays a role in mediating the relationship between knowledge-based HRM practice and structural capital and innovation performance, but it fails to mediate the relationship between knowledge-based HRM practice and relational capital. In addition, this research also proves that structural capital can mediate the relationship between knowledge-based HRM practice and innovation performance. Intellectual capital can affect innovation performance. Finally, knowledge-based HRM practice and human capital cannot influence relational capital, so relational capital cannot mediate the relationship between knowledge-based HRM practice and innovation performance.